Respuesta :

Answer:

[tex]Average\ Rate = -0.4[/tex]

Step-by-step explanation:

Given: The table

Required: Determine the average rate of change over [-3,2]

This is calculated as:

[tex]Average\ Rate = \frac{h(b) - h(a)}{b - a}[/tex]

In this case:

b = 2 and a = -3

So, we have:

[tex]Average\ Rate = \frac{h(2) - h(-3)}{2 - (-3)}[/tex]

[tex]Average\ Rate = \frac{h(2) - h(-3)}{2+3}[/tex]

[tex]Average\ Rate = \frac{h(2) - h(-3)}{5}[/tex]

From the table:

[tex]h(2) = 0[/tex]

[tex]h(-3) = 2[/tex]

Substitute these values in the above expression:

[tex]Average\ Rate = \frac{h(2) - h(-3)}{5}[/tex]

[tex]Average\ Rate = \frac{0 - 2}{5}[/tex]

[tex]Average\ Rate = \frac{-2}{5}[/tex]

[tex]Average\ Rate = -0.4[/tex]

ACCESS MORE